TPACK-Based Analysis of Prospective Physics Teachers’ Readiness for Digital Classroom Management - Linda Dwi Astuti; Permatasari, Indhah; Daru Wahyuningsih (Schrödinger: Journal of Physics Education, 2025)
Purpose of the study: This study aims to analyze the readiness of prospective physics teacher students in managing digital classrooms based on the TPACK framework, focusing on different semester levels (2nd, 4th, and 6th semesters) in the Physics Education Study Program at Sebelas Maret University. Methodology: A quantitative survey design was employed using a validated questionnaire based on TPACK indicators (TK, PK, CK, TPK, TCK, PCK, and TPACK). The instrument was measured with a five-point Likert scale. Data were analyzed using descriptive statistics, assumption testing (Shapiro–Wilk, Levene), ANOVA, and non-parametric tests with SPSS software. Main Findings: Results showed that students’ average readiness scores in TPACK dimensions increased from the 2nd to the 6th semester. Significant improvements were observed particularly between the 2nd and 6th semesters in dimensions such as TK, TPK, and TCK. However, not all semester comparisons showed statistically significant differences, indicating gradual but uneven development of TPACK competencies across cohorts. Novelty/Originality of this study: This study provides one of the first empirical analyses of TPACK readiness specifically among prospective physics teachers in Indonesia across different semester levels. The findings highlight how extended exposure to digital classroom practices strengthens TPACK competencies, offering insights for curriculum design that address semester-based progression in teacher education programs.